Hierarchical Mo9Se11 nanoneedles on nanosheet with enhanced electrochemical properties as a battery-type electrode for asymmetric supercapacitors - Rajan, Jose; Radhiyah, Abd Aziz; Saifful Kamaluddin, Muzakir; Izan Izwan, Misnon; Jamil, Ismail (Elsevier Ltd, 2016)
A hierarchical nanostructure of orthorhombic Mo9Se11 is synthesized by colloidal processing and evaluated for its application as an electrode for asymmetric supercapacitors (ASCs). The material is characterized by X-ray and electron diffraction, X-ray photoelectron spectroscopy, gas adsorption studies, scanning and transmission electron microscopies for their crystal structure, surface and morphological properties. These studies show that colloidal synthesized Mo9Se11 has a hierarchical structure in the form of nanoneedles grown on its nanosheet. The nanoneedles are single crystalline with circular cross-section of diameter ∼10–20 nm at the root, ∼6–10 nm at the tip and length ∼5–10 μm. Electrochemical properties of the material are studied in detail in three moderately conductive alkaline electrolytes, viz. 3 M of LiOH, NaOH, and KOH employing cyclic voltammetry, galvanostatic charge discharge cycling, and electrochemical impedance spectroscopy. The Mo9Se11 electrodes showed superior specific capacitance (CS ∼510 F g−1) and larger voltage window (up to 0.7 V) in the LiOH electrolyte. We show that the excellent electrochemical properties of Mo9Se11 can be assigned to the hierarchical microstructure and its one-dimensional channel structure; those accommodate and facilitate fast redox reactions for electrons and ions. Furthermore, ASCs were fabricated using the Mo9Se11 as a battery-type electrode and commercial activated carbon as supercapacitor electrode; the devices showed larger voltage window, energy density (ES), and power density (PS) than many of the devices reported in literature. The ASCs showed six times higher ES while maintaining similar PS than a control supercapacitor fabricated using activated carbon(AC).